Government's Dilemma: The Role of Government in Imitation and Innovation - Mahmood, Ishtiaq P.; Rufin, Carlos (Academy of Management Review, 2005)
We consider the role of government in the process of technological development, showing that the role of government regarding technological development varies over the development process. When a country is far from the technological frontier, the government can spur economic development through the centralization of economic and political control, but as the economy approaches the technological frontier, government's role must change considerably, political and economic freedom being necessary. In addition, domestic business groups can act as substitutes for governmental intervention, and multinational corporations can supplement governmental efforts.